Before the coffee gets cold : tales from the cafe - Kawaguchi, Toshikazu, 1971-; Trousselot, Geoffrey (London : Picador, an imprint of Pan Macmillan, 2020)
In a small back alley in Tokyo, there is a cafe which has been serving carefully brewed coffee for more than one hundred years. But this coffee shop offers its customers a unique experience: the chance to travel back in time ... From the author of Before the Coffee Gets Cold comes a story of four new customers each of whom is hoping to take advantage of Cafe Funiculi Funicula's time-travelling offer. Among some faces that will be familiar to readers of Kawaguchi's previous novel, we will be introduced to:The man who goes back to see his best friend who died 22 years agoThe son who was unable to attend his own mother's funeralThe man who went back to see the girl who he could not marryThe old detective who never gave his wife that gift ... This beautiful, simple tale tells the story of people who must face up to their past, in order to move on with their lives. Kawaguchi once again invites the reader to ask themselves: what would you change if you could travel back in time?--
Originally published in Japan by Sunmark Publishing in 2017.
Donated by Farhana Zahir, Assistant Professor, BRAC Business School
Translated from the Japanese.
Keywords: Coffeehouses -- Japan -- Tokyo -- Fiction; Time travel -- Fiction; Interpersonal relations -- Fiction; Japanese fiction